A new late Cenozoic species of Abertella (Echinoidea: Clypeasteroida) from Patagonia - Kroh, Andreas (2013)
A new species of abertellid sand dollar, Abertella miskellyi n. sp., is described from the Miocene Camarones Formation of Patagonia, southern Argentina. The new taxon corroborates the existence of the genus in South America, given that Abertella is most common in the southeastern USA and the eastern coast of Central America. It is characterized by a unique basicoronal circle, in which the interambulacral basicoronal plates are very heterogeneous in size (small in interambulacrum 5, largest in interambulacra 2 and 3). Additionally, it features disjunct oral interambulacra involving two ambulacral plates in some of the interambulacra rather than one, thus being the most disjunct of all known species of Abertella. A key to the species of the genus is provided.